2017
DOI: 10.1039/c7tb00052a
|View full text |Cite
|
Sign up to set email alerts
|

Upper critical solution temperature thermo-responsive polymer brushes and a mechanism for controlled cell attachment

Abstract: We report the synthesis of thermo-responsive polymer brushes with Upper Critical Solution Temperature (UCST)-type behaviour on glass to provide a new means to control cell attachment. Thermoresponsive poly(N-acryloyl glycinamide)-statpoly(N-phenylacrylamide) (PNAGAm-PNPhAm) brushes with three different monomer ratios were synthesized to give tunable phase transition temperatures (Tp) in solution. Surface energies of surface-grafted brushes of these polymers at 25, 32, 37 and 50 C were calculated from contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 37 publications
(35 reference statements)
5
46
0
Order By: Relevance
“…[ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ). Such (co)polymers have been mainly prepared using free radical polymerization [ 11,14–17,26 ] and by thermally initiated controlled radical polymerization such as atom transfer radical polymerization [ 13 ] and reversible addition fragmentation chain transfer (RAFT) [ 11,12,16–19,25 ] The impacts of various parameters on the UCST phase transition, including salts, pH, molecular weight, molecular weight distribution, and chemical composition, have been well evaluated.…”
Section: Figurementioning
confidence: 99%
“…[ 11–21 ] The non‐ionic polymers have attracted a great deal of attention due to their insensitivity to salts, which make them more attractive for applications in physiological environment. [ 22–24 ] During the last decade, efforts have been focused toward developing novel water‐soluble copolymers exhibiting UCST behavior by copolymerizing H‐donor monomers ( N ‐acryloyl glycinamide [ 11–16 ] or acrylamide [ 15,17–21,25 ] ) and H‐acceptor monomers (acrylonitrile, [ 11,15,18,19,21,25,26 ] styrene, [ 15,17 ] and butyl acrylate [ 15 ] ). Such (co)polymers have been mainly prepared using free radical polymerization [ 11,14–17,26 ] and by thermally initiated controlled radical polymerization such as atom transfer radical polymerization [ 13 ] and reversible addition fragmentation chain transfer (RAFT) [ 11,12,16–19,25 ] The impacts of various parameters on the UCST phase transition, including salts, pH, molecular weight, molecular weight distribution, and chemical composition, have been well evaluated.…”
Section: Figurementioning
confidence: 99%
“…In an another study, brushes of UCST-type poly (N-acryloyl glycinamide)-co-poly(N-phenylacryl amide) (PNAGAm-PNPhAm) were prepared for temperature controlled NIH-3T3 cells attachment and detachment. It was observed that cells were attached on the precipitated PNAGAm-PNPhAm brush surface after 20 h of incubation at 30°C (below UCST), whereas cells were detached from the surface within 2 h when the temperature of culture was increased and maintained at 37°C (Figure 19) [73]. N-succinimidyl N-methylcarbamate modified poly(l-ornithine)-co-poly(l-citrulline) copolymer with UCST of ~39°C was also evaluated for temperature mediated cell adhesion and detachment.…”
Section: Functional Cell Culturesmentioning
confidence: 99%
“…Phase contrast microscopy images of NIH-3T3 cells (a) attached to the polymer brush surface at 30°C and (b) detached from surface at 37°C. Reproduced with permission from reference[73], Copyright © 2017, The Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…In recent years, thermo-responsive surfaces 7,8 have been used as supports for mammalian cell culture, as their changes in physicochemical properties at upper or lower critical solution temperatures (UCST, LCST) can facilitate cell detachment without the need for enzymatic passaging. [9][10][11][12][13] PNIPAM is the most commonly used thermo-responsive polymer, however, the presence of strong hydrogen bond donors and hydrogen acceptors in its structure can lead to inter-and intra-chain association entanglement. 14 By comparison, PEG-based polymers have a reversible phase transition that occurs without chain entanglement.…”
Section: Introductionmentioning
confidence: 99%